(3ebGdI aj GdgjGJs - (3LGdjfhSs ((3Nda Hf CHj GdQHjY s)
(3ChdgG (B:s
(3bGd LGdjfhS bO Xf cKjQ ef GdCWHGA hGdadGSaI GdbOeGA Cf CYOd CeRLI GdHOf CaVd gjGJg s
(3BNQgG (B:s
(3aEPG cGf GdCeQ Ydi gPG ajLH Cf fVY CaVd GdgjGJ ai gPjf GdTjFjf CYfi ai EYJOGd eRGL GdCYVGA JeJ ebGdI LGdjfhS s
(3Vef eLehY , JQJjHgG (B: (3GdebGdI GdKGefIs
(3bQf GdfSN (B:s
(3GdbQf GdNGeSs
(3JHUQGJ GdCUd (B:s
(3GdfSNI ebQhAI ef YGde eYQha (B: (3Ydi GdTjN CHj GdaVd GdeWgQ Hf CMeO GdCUHgGfi SfIs
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs